Analisis Pengelolaan dan Efektivitas Zakat Produktif terhadap Pemberdayaan Pedagang Kaki Lima: Studi pada BAZNAS Kota Jambi - Maryani; Wijaya, Deni; Angre Yani, Fitri; Zaini Ladista, Aldri; Dwi Andreanto, Agung; Suri Barus, Supian (Journal of Islamic Economic Studies, 2025)
This study aims to analyze the management and effectiveness of productive zakat distributed by the National Amil Zakat Agency (BAZNAS) of Jambi City in empowering street vendors. Productive zakat is viewed as a strategic instrument for transforming mustahik (zakat recipients) into muzakki (zakat payers) through enhanced business capacity and income growth. This research employs a normative-empirical approach with a qualitative descriptive method, combining legal analysis of zakat regulations—particularly Law Number 23 of 2011 on Zakat Management and BAZNAS regulations—with field data obtained through interviews and observations involving administrators and beneficiaries. The results indicate that the management of productive zakat at BAZNAS Jambi City has been in accordance with Islamic law principles and positive legal norms, encompassing planning, distribution, mentoring, and evaluation stages. However, its effectiveness in economic empowerment remains suboptimal due to limited capital, insufficient business assistance, and low financial literacy among beneficiaries. This study concludes that enhancing managerial capacity and continuous mentoring are key to achieving the objectives of productive zakat in accordance with maqāṣid al-syarī‘ah, particularly in preserving wealth (ḥifẓ al-māl) and promoting social welfare.